Allotetraploid evolution in Dactylorhiza (Orchidaceae) - Chase, Mark (2015)
One of the most perplexing problems in Western European terrestrial orchid taxonomy has been how to deal with the large numbers of taxa that have been described for the allopolyploid taxa, which are the products of hybridization between taxa in the Dactylorhiza maculata (L.) Soó group and the D. incarnata (L.) Soó group.